STATISTICAL CHARACTERIZATION OF GROUNDWATER QUALITY IN THE BISKRA REGION, NORTHEASTERN ALGERIA - Nemili Zohra; Baazi Houria; Necer AbdeLdjabar; Saoudi Messaoud (International Journal of Innovative Technologies in Social Science, 2024)
The main objective of this work is to characterize the groundwater quality in the Biskra region using Principal Component Analysis (PCA) on 59 samples from the most heavily exploited boreholes in the study area, more specifically those used for human consumption. The PCA results showed two axes that explain 70.8% of the information, with axis F1 summarizing 60.86% of the information and describing the parameters related to mineralization (EC, HCO3, TH, Ca+2, Mg+2, Cl-, SO4, K, Na), while axis F2 presents 9.9% of the initial information and describes a weak correlation of nitrates concerning all other parameters, which confirms its origin given the proximity of agricultural land and industrial zones for certain boreholes. To this end, continuous monitoring of water quality is mandatory, as is the implementation of treatment to reduce water quality degradation and eliminate health problems.